National Action Plan for Agriculture GHG Inventory Improvement The Bahamas - Stevens, Luanne (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
The IICA-GCF Readiness Project is aimed at improving climate action in the agricultural sector in nine Caribbean countries. It improves the agriculture GHG inventory by assessing the status of the national inventory, identifying areas for development, developing actions for improvement, and prioritizing the actions. The project team conducted a review of The Bahamas' latest agriculture GHG inventory to identify institutional arrangements, data sources, collection procedures, quality control and verification procedures, and tools utilized for inventory compilation. Additionally, it worked with national experts to improve the agriculture GHG inventory compilation process in each country.